Effect of durian peel fiber on thermal, mechanical, and biodegradation characteristics of thermoplastic cassava starch composites - Jumaidin, Ridhwan; Low, Yong Whang; Rushdan, Ahmad Ilyas; Kamaruddin, Zatil Hazrati; Kamaruddin, Zatil Hafila; Jamal, Tarique; Aziz, Alia Ruzanna (Elsevier B.V., 2023)
This study is focused on developing and enhancing the properties of durian peel fiber (DPF) reinforced thermoplastic cassava starch (TPCS) composites. The proposed DPF was extracted from agro-waste and incorporated into TPCS with various contents of DPF (10, 20, 30, 40, and 50 wt%) via compression molding. The mechanical and thermal characteristics of the fabricated composites were studied. The thermal properties of the biocomposite were improved with the addition of DPF, as evidenced by an increase in the material's thermal stability and indicated by a higher onset decomposition temperature. The integration of DPF into TPCS improved the biodegradation rate process of the composites. Besides, the results indicated that incorporating DPF in TPCS composites enhanced tensile and flexural properties, with a 40 wt% DPF content exhibited the highest modulus and strength. The tensile and flexural strengths of TPCS/DPF composites were raised significantly from 2.96 to 21.89 MPa and 2.5 to 35.0 MPa, respectively, compared to the control TPCS sample, as DPF increased from 0 to 40 wt%. This finding was consistent with Fourier-Transform Infrared (FT-IR) spectroscopy and scanning electron micrograph (SEM), which showed good interaction between DPF and TPCS matrix. The analysis revealed that DPF at a 40 wt% ratio was the best composition compared to the other ratio. Finally, based on improved results, DPF was identified as a potential resource of green reinforcement for the biodegradable TPCS matrix.